Content and network analysis of tweets tagged with #aphasia: an emergent community of practice. Issue 8 (3rd August 2021) - Bryant, Lucy; Brunner, Melissa; Power, Emma; Hemsley, Bronwyn
ABSTRACT: Background : A reduced quality of life for people with aphasia is in part associated with their loss of friendships and social networks. Twitter offers people with communication disability a way to exchange information, develop and maintain their social networks and connections, and participate in society online. However, little is known about how Twitter is used to exchange information about aphasia or to build communities online that might support people with aphasia in their communication goals. Aims : To examine the network data and content of tweets tagged with #aphasia to understand more about how Twitter is used by people with aphasia, aphasia organisations, aphasiologists, clinicians, and the public. Method : A Twitter hashtag study was conducted to locate tweets highly relevant to aphasia. A daily tweet capture using the Twitter search bar was conducted for one month, November 2018, searching for publicly available tweets tagged with aphasia-related hashtags. The tweets collected were analysed using both qualitative and quantitative methods. Results : A sample of 2, 519 tweets were included in the analysis. The sample comprised 865 original tweets and 1, 654 retweets which included "quote tweets", sent by 839 unique Twitter @Users. Tweet content reflected users discussing aphasia research, exchanging health information, advice and inspiration, providing personal stories, raising awareness about aphasia, and an emergent aphasia community online. Conclusion : The aphasia community in Twitter is relatively small compared to other communities focused on communication disability and is emergent in terms of its size and the strength of connections. The majority of people or organisations tweeting about aphasia, and hence influencing the network, were health professionals working in the field of aphasia. There was minimal conversational interaction evident. These results demonstrate that Twitter is underutilised as a platform for interaction and engagement in relation to aphasia, and further research is needed.